Adding Value To Lix / Sx / Ew Operations By Recovering Copper From Bleed, Raffinate And Other Plant Streams - E. R. Dixon (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
Copper SX/EW plants often bleed part of their electrowinning electrolyte to control impurities and maintain consistent cathode quality. Depending on the specific situation at each site, the bleed is either returned to raffinate, to an SX extraction stage, to an SX wash stage, or to the PLS pond, to avoid losing the copper in the bleed. This practice can have undesirable effects on the overall process. An alternative is to electrowin all or most of the copper in the bleed, thus avoiding the recirculation of the copper in the bleed. In this manner, the bleed is converted to metallic copper without interfering with the SX circuit. This in turn reduces the copper concentration in the raffinate, improving global copper recovery because of improved leaching conditions.